Pricing initial public offerings in premature capital markets: The case of Hungary - Ibolya Schindele; Enrico C. Perotti (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper investigates the determinants of underpricing at initial public offerings in theHungarian Initial Public Offerings (IPO) market in 1990–1998, a period of transition from socialist to market economy and immaturity of the domestic capital market. The evidence suggests that political issues played a significant role in the process: we have found greater discount at privatization IPOs than at private issues, and a positive relation between underpricing and the proportion of shares offered for compensation coupons. These findings reinforce the hypothesis that governments in transition may pursue political objectives by selling shares at discount. Besides, the results show larger initial returns at early IPOs compared to later issues, which implies a negative relation between the discount and the maturing of the capital market. Most of the asymmetric information theories, empirically justified for well-developed stock markets, receive no support. Some results suggest that the transition related determinants of underpricing disappear as the securities market becomes more mature.
Keywords: L33; G14; 330; Initial public offerings; underpricing; privatization; Börsengang; Emissionskurs; Finanzmarkt; Ungarn